Comparison of safety and outcomes of shock wave lithotripsy between elderly and non-elderly patients - Chen YZ (Dove Medical Press, 2017)
Yi-Zhong Chen,1 Wun-Rong Lin,1,2 Chih-Chiao Lee,1,2 Fang-Ju Sun,1,3 Yung-Chiong Chow,1,2 Wei-Kung Tsai,1,2 Pai-Kai Chiang,1,2 Ting-Po Lin,1,2 Marcelo Chen,1–3 Allen W Chiu1,4 1Department of Urology, MacKay Memorial Hospital, 2School of Medicine, MacKay Medical College, 3Department of Cosmetic Applications and Management, MacKay Junior College of Medicine, Nursing and Management, 4School of Medicine, National Yang-Ming University, Taipei, Taiwan Background: This study compared the clinical outcomes of extracorporeal shock wave lithotripsy between elderly (aged ≥65 years) and non-elderly (aged <65 years) patients.Methods: A retrospective review of medical records was performed on 483 (non-elderly: 245, elderly: 238) patients with upper urinary tract stones who underwent shock wave lithotripsy between 2007 and 2015. The demographic data, stone parameters, stone-free rate, retreatment rate, and complication rate were analyzed in both elderly and non-elderly patient groups.Results: There was no significant difference between non-elderly and elderly patients in terms of stone-free rate (46.5% vs 41.1%, P>0.05) regardless of stone site or stone size and overall retreatment rate (41.6% vs 37.0%, P>0.05). Elderly patients had a higher complication rate than non-elderly patients (15.5% vs 23.5%, P=0.026). The most common complication was flank pain. Receiver operating characteristic curves predicted that elderly patients (cutoff value: 65 years of age) had a higher risk of complications and that patients with smaller stones (cutoff value: 0.8 cm) had a higher stone-free rate.Conclusion: This study showed that elderly patients with upper urinary tract stones undergoing shock wave lithotripsy had comparable efficacy for stone-free rates and retreatment rates, but higher complication rates. Keywords: elderly, shock wave lithotripsy, upper urinary tract stone, safety, outcome